RAJAH DALAM TRADISI MASYARAKAT ACEH - Rizka utami; Nisa Auliana (TASHWIR, 2024)
Abstract: Some people in Aceh believe that there are individuals who possess the ability to call upon guardian spirits or khadam that protect them. This is known as "rajah," which is understood as a mantra and prayer, or symbols such as tattoos in certain tribes. This article employs a qualitative approach with ethnographic methods and a sociological perspective. The research findings indicate that Rajah is a form of traditional healing that combines spiritual and symbolic elements, usually performed by individuals considered to have special skills, such as shamans or spiritual experts. In the context of magical healing, rajah is used to counter or neutralize negative energy that may be sent through supernatural means, such as black magic, curses, witchcraft, or peunyaket donya, a term unique to Aceh referring to diseases caused by the malevolent intentions of others. This process typically involves the writing of specific symbols, recitations of prayers, or mantras that are believed to possess the power to protect or heal. The practice aims not only to address physical issues but also to restore the spiritual balance of a person believed to be disturbed by negative energy. In Acehnese culture, peunyaket donya reflects the belief in the influence of magic in daily life, a belief still held by some members of the community. Keywords: Aceh community, Rajah Abstrak:Sebagian masyarakat Aceh percaya bahwa ada individu yang memiliki kemampuan untuk memanggil roh penjaga atau khadam yang melindungi dirinya. Hal tersebut dikenal dengan ungkapan rajah yang dimaknai sebagai mantra dan do’a atau simbol-simbol seperti tato pada suku tertentu. Artikel ini menggunakan pendekatan kualitatif dengan metode etnografi dan pendekatan sosiologi. Hasil penelitian menunjukkan bahwa Rajah merupakan salah satu bentuk pengobatan tradisional yang memadukan elemen spiritual dan simbolik, biasanya dilakukan oleh individu yang dianggap memiliki keahlian khusus, seperti dukun atau ahli spiritual. Dalam konteks pengobatan magis, rajah digunakan untuk melawan atau menetralkan energi negatif yang bisa dikirimkan melalui cara-cara gaib, seperti teluh, guna-guna, santet, atau peunyaket donya, yang merupakan istilah khas Aceh untuk penyakit yang disebabkan oleh niat jahat orang lain. Proses ini biasanya melibatkan penulisan simbol tertentu, bacaan doa, atau mantra yang diyakini memiliki kekuatan untuk melindungi atau menyembuhkan. Tujuan praktik ini tidak hanya untuk mengatasi masalah fisik, tetapi juga untuk memulihkan keseimbangan spiritual seseorang yang diyakini terganggu oleh energi negatif. Dalam budaya Aceh, peunyaket donya mencerminkan keyakinan terhadap pengaruh magis dalam kehidupan sehari-hari, yang masih diyakini oleh sebagian masyarakat. Kata Kunci: Masyarakat Aceh, Rajah